Implication of Rural Population in Planning Local Community Development: A Need for Policy Reform - Engwali, Fon Dorothy; Grace , Mengue Melongo Priscille (Asian Journal of Agriculture and Rural Development, 2019)
It has been observed that the participation of rural population is not really massive in some localities during the process of planning local community development. Thus, this study seeks to identify factors which can influence the participation of an individual in the materialization of the planning process at the level of the village. Data was collected from 108 respondents with the help of a structured pre-tested questionnaire in Bonalea and Dibamba councils. The binary logistic regression was used to find the factors which can influence their participation in the planning process. The results show that the implication of an individual is influenced by his or her affiliation (membership) to a farmer’s organization and the knowledge that a person has about the activities of the program. This suggests the need for the government to increase the sensitization about the activities of the program and the benefit of being a member of a farmer’s organization. The origin of the family influenced their participation. A non-native of a locality does not find it important to take part in any development process in their host locality which therefore suggests the need for the government to realize a special plan for strangers in locality.